APLIKASI SEVEN TOOLS QUALITY CONTROL DALAM PENGENDALIAN MUTU CRUDE PALM OIL (CPO) DI TANGKI TIMBUN PABRIK KELAPA SAWIT - Purwanto, Heri; Mahyunis; Hartanti, Puspita Sri (Institut Teknologi Sawit Indonesia (ITSI), 2025)
Quality control of Crude Palm Oil (CPO) is essential to ensure compliance with quality standards. This study aims to control and analyze CPO quality parameters, namely Free Fatty Acid (FFA), moisture content, and dirt content, using the Seven Tools of Quality Control. The research was conducted at a palm oil mill in South Labuhanbatu Regency, North Sumatra, using laboratory quality data collected from October to December 2024. A descriptive quantitative method was applied by utilizing check sheets, Pareto diagrams, control charts, and fishbone diagrams within the Quality Control Circle (QCC) approach. The results showed that quality deviations occurred in 28 samples for FFA, 22 samples for dirt content, and 14 samples for moisture content. Pareto analysis indicated that FFA and dirt content were the main contributors to quality problems, accounting for 78.13% of total deviations. Control chart analysis revealed several periods of process instability, particularly in FFA values. The study concludes that the Seven Tools of Quality Control are effective in identifying dominant quality problems and supporting improvement efforts to enhance CPO quality.